Oral manifestations of diabetes mellitus: an integrative review (Research, Society and Development, 2023)
Diabetes Mellitus (DM) is a chronic disease characterized by insufficient insulin not produced by the pancreas or by the body's inability to use it, which can lead to hyperglycemia. The metabolic alterations resulting from decompensated DM generate consequences throughout the body, consequently affecting oral health as well. Therefore, it is imperative that dentists are aware of these manifestations in order to provide better dental treatment. In this sense, the aim of this study was to describe the main oral manifestations associated with diabetes mellitus through an integrative literature review. Thus, a search was carried out in the PubMed/Medline, Lilacs and SciELO databases, reaching the final selection of 12 articles for this work. The results revealed a high prevalence of oral alterations such as xerostomia, dental caries, periodontal disease and stomatitis in patients with DM. Thus, it was found that DM is associated with oral manifestations such as salivary, dental, periodontal and soft tissue alterations. Therefore, the importance of the dentist in the early diagnosis and/or control of possible complications associated with DM is clear.